Evaluation of risk factors for 14-day and 30-day mortality among treatment regimens against Pseudomonas aeruginosa resistant to carbapenem but susceptible to traditional antipseudomonal non-carbapenem β-lactam agents. - Suvadee Supreeyasakon; Jantima Traipattanakul; Jatapat Hemapanpairoa; Piraporn Juntanawiwat; Wichai Santimaleeworagun (PLoS ONE)
Pseudomonas aeruginosa associated with hospital-acquired infection is often resistant to various antibiotics and is associated with high mortality worldwide. The appropriate treatment of Pseudomonas aeruginosa resistant to carbapenems but susceptible to traditional antipseudomonal non-carbapenem β-lactam agents (Car-R/NonCar-S P. aeruginosa) remains unclear. This retrospective study evaluated risk factors for 14-day and 30-day mortality among treatment regimens against Car-R/NonCar-S P. aeruginosa. This study enrolled 180 patients with Car-R/NonCar-S P. aeruginosa infection at Phramongkutklao Hospital between January 2019 and December 2023. The 14-day and 30-day mortality rates were 18.3% and 28.9%, respectively. Bloodstream infection (OR 1.97, 95% CI 0.88-4.43), septic shock (OR 3.3, 95% CI 1.30-8.40), Acute Physiology and Chronic Health Evaluation (APACHE) II < 14 (OR 0.13, 95% CI 0.03-0.54), Sequential Organ Failure Assessment (SOFA) <7 (OR 0.25, 95% CI 0.11-0.56), and Pitt bacteremia score <4 (OR 0.16, 95% CI 0.05-0.47) were associated with 14-day mortality. There was a higher 14-day and 30-day mortality in patients treated with piperacillin/tazobactam or aminoglycosides but there was no significant difference among antipseudomonal antimicrobial agents in the treatment of Car-R/NonCar-S P. aeruginosa infection. We supported the use of traditional antipseudomonal β-lactam agents to treat Car-R/NonCar-S P. aeruginosa infections, however the use of piperacillin/tazobactam might be concerned in some cases and further investigations were needed.